Pengaruh Senam Nifas Terhadap Penurunan Tinggi Fundus Uteri Pada Ibu Post Partum - Fadlina, Amelia, Dwi Rosella K, S.Fis.,Ftr.,M.Fis, Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background: Uterine involution is a normal diminution of an organ after it is completed its functions, such as the downsizing of the uterus after childbirth. Uterine involution is a shrinking back in the uterus after childbirth back to forms of the origin. Provision of the therapeutic modalities for uterine fundus decrease selected is the gymnastics of parturition. Objective: To determine the effect of post natal gymnastics toward the decrease of uterine fundus involution at Health Clinic "Ngudi Waras" Makamhaji Sukoharjo. Methods: This study used a Quasi Experimental with Single Case Research. Population in this research is the post partum mother at Makam Haji, the number of sample were 2 people. Pain measurement was done by using Pelvimeter (CM) with the total respondont of 2 people. The results were analyzed by using descriptive analytic study. Results: Based on the analytical descriptive study, it is obtained a significant results with values of 6.86% and 5.71% which means that there is an effect of post natal gymnastics toward the decrease of maternal uterine fundus involution post partum. Conclusion: Post natal Gymnastics has been proven to give effect toward the decrease of maternal uterine fundus involution post partum.